2019
DOI: 10.1523/jneurosci.0487-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Microglial P2Y12 Receptor Regulates Seizure-Induced Neurogenesis and Immature Neuronal Projections

Abstract: Seizures are common in humans with various etiologies ranging from congenital aberrations to acute injuries that alter the normal balance of brain excitation and inhibition. A notable consequence of seizures is the induction of aberrant neurogenesis and increased immature neuronal projections. However, regulatory mechanisms governing these features during epilepsy development are not fully understood. Recent studies show that microglia, the brain's resident immune cell, contribute to normal neurogenesis and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 82 publications
(115 reference statements)
7
57
0
Order By: Relevance
“…Again, when P2RY12 was ablated, microglia were unable to respond to the hyperactivity, and mice exhibited severe epileptic seizures 60 . Microglia P2RY12 signaling is also linked to aberrant seizure-induced neurogenesis 61 . As recent studies have outlined substantial neuronal-neoplastic communication in GB 62,63 , the presence of non-uniform populations of P2RY12 + F4/80 High peritumoral microglia, and mature neurons at the glioma leading edge suggests that a potential tripartite system exists including neurons, glioma, and myeloid cells.…”
Section: Discussionmentioning
confidence: 99%
“…Again, when P2RY12 was ablated, microglia were unable to respond to the hyperactivity, and mice exhibited severe epileptic seizures 60 . Microglia P2RY12 signaling is also linked to aberrant seizure-induced neurogenesis 61 . As recent studies have outlined substantial neuronal-neoplastic communication in GB 62,63 , the presence of non-uniform populations of P2RY12 + F4/80 High peritumoral microglia, and mature neurons at the glioma leading edge suggests that a potential tripartite system exists including neurons, glioma, and myeloid cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, it has been shown that microglia mediate synapse loss, neuronal loss, and memory impairment in Alzheimer's disease (overview in [49] and [50]); mediate dopaminergic injuries via the NF-ÎșB signaling pathway in Parkinson's disease [51]; or provide an environment for the initiation of T-cell cytotoxicity in Rasmussen encephalitis [52]. On the other hand, microglia can equally mediate protective effects such as reducing spreading depolarization and calcium overload [53], eliminating neutrophil invasion in brain ischemia [54], promoting seizure-induced neurogenesis [55], or maintaining the vascular integrity under hypoxia conditions [56]. In connection with MS, it has been shown that phagocytosis of myelin debris by the microglia is a prerequisite for endogenous remyelination [57,58], but the cells can also induce a core oxidative stress gene signature when activated, which leads to axonal damage [59].…”
Section: General Aspects Of Ms Pathology and The Relevance Of Glial Cmentioning
confidence: 99%
“…After intracerebroventricular or intraperitoneal injection of KA, the seizures are exacerbated in P2Y12Rdeleted rats [121]. The microglial P2Y12Rs are also essential for microglia-neuron interactions in mice with KA-induced epilepsy [122]. Another study shows that microglia can use TLR9 to sense self-DNA released by dying neurons, and then secrete TNF-α, thus inhibiting the proliferation of neural stem cells (including granules cells in epileptic zones), which would attenuate the aberrant neurogenesis [123,124].…”
Section: Classic Pro-inflammatory Cells In Epilepsymentioning
confidence: 99%
“…P2Y6Rs and P2Y12Rs can activate microglia by interacting with UDP and ATP, respectively [143]. After the occurrence of acute epileptic insults, microglia can play a neuroprotective role mainly through P2Y12Rs [121,122], and it has been found that the microglial P2Y12Rs are necessary for the microglia-neuron interactions in KA-treated epilepsy mice [122]. However, the roles of certain P2YRs can be divergent depending on specific downstream pathways.…”
Section: P2rsmentioning
confidence: 99%